OPTIMALISASI KINERJA SEBAGAI PELAYANAN MASYARAKAT TERHADAP PELAKSANAAN VAKSIN COVID-19 BERDASARKAN PASAL 25 AYAT 3 HURUF C PERATURAN PEMERINTAH NOMOR 17 TAHUN 2018 TENTANG KECAMATAN (Studi Di Kelurahan Durian Payung, Tanjung Karang Pusat) - SYAHPRI DJUNISAR; Rusli Tami (KEADILAN PROGRESIF, 2022)
Health is one of the elements of general welfare that needs to be realized in accordance with the ideals of the Indonesian people as referred to in the 1945 Constitution. Various kinds of certain infectious diseases can be prevented through the availability of vaccinations to prevent the transfer of disease from one region to another in a relatively short time. short and effective. The problem in this study is the optimization of performance as a public service for the implementation of the covid-19 vaccine based on Article 25 Paragraph 17 of 2018 concerning sub-districts in the durian umbrella village, Tanjung Karang center and the inhibiting factor for optimizing performance as a public service for the implementation of the covid-19 vaccine based on Article 25 Paragraph 17 of 2018 concerning sub-districts in the Durian Umbrella Village, Tanjung Karang, Central. The research method uses a normative juridical approach and an empirical approach using secondary data and primary data, then qualitative juridical data analysis is carried out. The results of the study, optimizing performance as a public service for the implementation of the Covid-19 vaccine based on Article 25 Paragraph 17 of 2018 concerning sub-districts in the Durian Umbrella Village to reduce the spread of the Covid-19 virus by providing public services in the form of making it easy to vaccinate to counseling the community about the program. government to prevent the spread of the virus. And the inhibiting factor for optimizing performance as a public service for the implementation of the covid-19 vaccine is the habit of people who are still indifferent to the government's recommendation to carry out the covid-19 vaccine, coupled with the slanted issue circulating among the public about the covid-19 vaccine, causing people not to do vansin. which has been recommended. Suggestions, the government must continue to carry out its duties as apublic service provider for the benefit of the community so that it changes government or private public services to focus on services that avoid an increase in the number of COVID-19 cases.